On the detection of a solar radio burst event that occurred on 28 August 2022 and its effect on GNSS signals as observed by ionospheric scintillation monitors distributed over the American sector - Wright, Isaac G.; Rodrigues, Fabiano S.; Gomez Socola, Josemaria; Moraes, Alison O.; Monico, João F. G. [UNESP]; Sojka, Jan; Scherliess, Ludger; Layne, Dan; Paulino, Igo; Buriti, Ricardo A.; Brum, Christiano G. M.; Terra, Pedrina; et al. (EDP Sciences, 2023)
As part of an effort to observe and study ionospheric disturbances and their effects on radio signals used by Global Navigation Satellite Systems (GNSS), alternative low-cost GNSS-based ionospheric scintillation and total electron content (TEC) monitors have been deployed over the American sector. During an inspection of the observations made on 28 August 2022, we found increases in the amplitude scintillation index (S4) reported by the monitors for the period between approximately 17:45 UT and 18:20 UT. The distributed, dual-frequency observations made by the sensors allowed us to determine that the increases in S4 were not caused by ionospheric irregularities. Instead, they resulted from Carrier-to-Noise (C/No) variations caused by a solar radio burst (SRB) event that followed the occurrence of two M-class X-ray solar flares and a Halo coronal mass ejection. The measurements also allowed us to quantify the impact of the SRB on GNSS signals. The observations show that the SRB caused maximum C/No fadings of about 8 dB-Hz (12 dB-Hz) on L1 ∼ 1.6 GHz (L2 ∼ 1.2 GHz) for signals observed by the monitor in Dallas for which the solar zenith angle was minimum (∼24.4) during the SRB. Calculations using observations made by the distributed monitors also show excellent agreement for estimates of the maximum (vertical equivalent) C/No fadings in both L1 and L2. The calculations show maximum fadings of 9 dB-Hz for L1 and of 13 dB-Hz for L2. Finally, the results exemplify the usefulness of low-cost monitors for studies beyond those associated with ionospheric irregularities and scintillation.
Keywords: Fading; GNSS; GPS; Solar radio burst; Space weather; SRB